Tathwir al-Ikhtibar al-Tashnifi li Kafaah al-Lughah al-'Arabiyyah li al-Thullab al-Judud - Moh. Supriyadi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
At Darul Lughah wad Dirasah al-Islamiyah, there is a placement test; however, this test is not based on proper language testing principles and is not comprehensive enough to measure students’ Arabic language proficiency. Therefore, the researcher intends to develop the format of the placement test so that it becomes better than the existing one. The objectives of this study are: (1) to develop a placement test for measuring students’ Arabic language proficiency ; and (2) to describe the quality of the developed placement test in terms of validity, reliability, discrimination index, and difficulty level. The research method used in this study is Research and Development (R&D) with a quantitative approach. The research population consists of students of Dar al-Lughah and Islamic Studies Institute. The researcher uses questionnaires and tests as data collection instruments. The results of the study are as follows: (1) The development of a placement test for students’ Arabic language proficiency. The developed placement test consists of 50 items out of a total of 100 items, covering vocabulary and grammar/structures, listening skill, writing skill, and reading skill. (2) The analysis of the developed placement test shows that: The level of validity is moderate, with 66.6% categorized as good and 33.3% categorized as acceptable. The level of reliability is excellent, with a coefficient of 0.989. The level of difficulty is moderate. The discrimination index of the developed placement test is categorized as good, with 26 items classified as good.